2015
DOI: 10.1159/000438670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Loudness Variation on Velopharyngeal Function in Children with 22q11.2 Deletion Syndrome: A Pilot Study

Abstract: Objective: Children with 22q11.2 deletion syndrome (22qDS) often require surgical intervention to treat velopharyngeal dysfunction (VPD). Although some studies have documented improved velopharyngeal (VP) closure under increased speaking effort, currently no studies have examined the effect of similar behavioral speech modifications on VP closure in children with 22qDS. The purpose of this pilot study was to explore the effect of loudness on VP closure during speech in children with 22qDS and persisting VPD. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A poorer postsurgical resonance rating observed in this report is likely related to the large increase in velopharyngeal orifice area (+80 mm 2 ); however, studies have suggested that other factors such as temporal variability and loudness may affect perceptual ratings of hypernasality and velopharyngeal orifice area (Warren et al, 1985; Warren et al, 1993; Warren et al, 1994; Cummings et al, 2015). The relationship between perceived severity of hypernasality and velopharyngeal gap size is nonlinear and studies have failed to demonstrate a strong correlation (Dalston and Seaver, 1990; Witt and D’Antonio, 1993; Baken and Orlikoff, 2000).…”
Section: Discussionmentioning
confidence: 53%
“…A poorer postsurgical resonance rating observed in this report is likely related to the large increase in velopharyngeal orifice area (+80 mm 2 ); however, studies have suggested that other factors such as temporal variability and loudness may affect perceptual ratings of hypernasality and velopharyngeal orifice area (Warren et al, 1985; Warren et al, 1993; Warren et al, 1994; Cummings et al, 2015). The relationship between perceived severity of hypernasality and velopharyngeal gap size is nonlinear and studies have failed to demonstrate a strong correlation (Dalston and Seaver, 1990; Witt and D’Antonio, 1993; Baken and Orlikoff, 2000).…”
Section: Discussionmentioning
confidence: 53%
“…In this regard, it must be emphasized that more nuanced structural anomalies underlie occult submucous clefts compared to classic “open” submucosal forms with Calnan triad (uvula bifida, soft palate muscle diastasis, palpable notch in hard palate). Therefore, occult submucous cleft anomalies can be exclusively identifiable through intra-operative surgical dissection and, as such, can only be presumed (position and insertion anomalies of the levator palati and/or uvula muscle; minimal alterations to the palatal bone posterior border) in non-operated cases after conventional clinical and instrumental examination [ 6 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The speech sample was recorded using the Voice Analysis module of the Daisy 3.6 program [ 13 ] (Biomedica Amplifon, Ripamonti, 133, 20141, Milano, Italy). Three experienced speech pathologists assessed and perceptually graded rhinolalia, rhinophony and nasal air escape, and repeated the same assessment after 15 days, according to the classification by Massari [ 17 ]. Each expert listened to the speech sample recordings of the 31 recruited individuals in a randomized order, for as long as necessary, for the purpose of perceptual evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the minimal effect of vocal loudness on nasalance was reported in children with cleft palate and varying degrees of hypernasality (Van Lierde et al, 2011). Despite the inconclusive acoustic findings, aerodynamic studies (McHenry, 1997; Cummings et al, 2015) suggest that increased loudness facilitates velopharyngeal closure overall in terms of reducing velopharyngeal orifice size in some patients with velopharyngeal dysfunction. Cummings et al (2015) further showed that increased vocal loudness decreased nasal airflow durations, suggesting that temporal gestures of velopharyngeal opening and closing may be altered by vocal loudness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inconclusive acoustic findings, aerodynamic studies (McHenry, 1997; Cummings et al, 2015) suggest that increased loudness facilitates velopharyngeal closure overall in terms of reducing velopharyngeal orifice size in some patients with velopharyngeal dysfunction. Cummings et al (2015) further showed that increased vocal loudness decreased nasal airflow durations, suggesting that temporal gestures of velopharyngeal opening and closing may be altered by vocal loudness. It is reasonable to hypothesize that vocal loudness changes may also affect the temporal domain of acoustic nasalization, which still needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%